2005
DOI: 10.1103/physrevlett.94.010601
|View full text |Cite
|
Sign up to set email alerts
|

Partially Asymmetric Exclusion Models with Quenched Disorder

Abstract: We consider the one-dimensional partially asymmetric exclusion process with random hopping rates, in which a fraction of particles (or sites) have a preferential jumping direction against the global drift. In this case, the accumulated distance traveled by the particles, x, scales with the time, t, as x approximately t(1/z), with a dynamical exponent z>0. Using extreme value statistics and an asymptotically exact strong disorder renormalization group method, we exactly calculate z(PW) for particlewise disorder… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(116 citation statements)
references
References 36 publications
3
113
0
Order By: Relevance
“…In the field of random walks, we have only described here the simplest models involving a single random walk in a disordered medium, but models involving many interacting random walks in the presence of quenched disorder can be also studied via the strong disorder approach [74], in particular reaction diffusion models [55,85], asymmetric exclusion processes [76], contact processes [70] and zero-range processes [77]. In the field of phase transitions of disordered polymer models, we have restricted our presentation here to the case of bidimensional wetting and of Poland-Scheraga model of DNA denaturation, but the idea to study the distribution of pseudo-critical temperatures allows to clarify the critical properties of other equilibrium transitions, such as the selective interface model [100] and the directed polymer transition in d = 3 [61] mentioned in the introduction (3).…”
Section: Discussionmentioning
confidence: 99%
“…In the field of random walks, we have only described here the simplest models involving a single random walk in a disordered medium, but models involving many interacting random walks in the presence of quenched disorder can be also studied via the strong disorder approach [74], in particular reaction diffusion models [55,85], asymmetric exclusion processes [76], contact processes [70] and zero-range processes [77]. In the field of phase transitions of disordered polymer models, we have restricted our presentation here to the case of bidimensional wetting and of Poland-Scheraga model of DNA denaturation, but the idea to study the distribution of pseudo-critical temperatures allows to clarify the critical properties of other equilibrium transitions, such as the selective interface model [100] and the directed polymer transition in d = 3 [61] mentioned in the introduction (3).…”
Section: Discussionmentioning
confidence: 99%
“…In [12] it is shown that the ASEP on a periodic system may be mapped onto a Zero Range Process and the condensation transition is fully discussed in the context of the Zero Range Process. Recently, further progress has been made in understanding the case where q µ = 0 by using extreme values statistics and renormalisation arguments [161].…”
Section: Bose-einstein Condensationmentioning
confidence: 99%
“…Also reaction-diffusion models [11] with quenched disorder might show strong Griffiths effects [12], see, however [13,14]. As an example we consider here the PASEP with particle-wise (pw) disorder [8], in which the i-the particle, i = 1, 2, . .…”
Section: Introductionmentioning
confidence: 99%
“…Another class of problems with strong Griffiths effects are stochastic many-particle systems [6]) with quenched disorder [7], such as the 1d partially asymmetric simple exclusion process (PASEP)) with position or particle dependent hopping rates [8,9] or the zero range process (ZRP) with disorder [10]. Also reaction-diffusion models [11] with quenched disorder might show strong Griffiths effects [12], see, however [13,14].…”
Section: Introductionmentioning
confidence: 99%